Emotive interjections in translation from Swedish into Polish - Sworowska, Anna (Papers in Linguistics, 2019)
Abstract: The aim of the article is to present the results of research conducted on the current Swedish-Polish corpus, which consists of contemporary literary texts translated into Polish in the years 2000-2017. Corpus, which is being elaborated in the Scandinavian Research Centre of the Institute of Applied Linguistics (ILS), University of Warsaw, currently consists of 4,700,000 units and is being expanded on a constant basis. In the research, interjections (Swedish ‘interjektioner’) occurring in the Swedish language (aj, oj, å(h), usch, fy, äsch, ack) and the text equivalents in Polish language have been compared and analysed using the concurrent data. One of the functions of interjections, both in Polish and Swedish, is the expression of emotions. Interjections communicate various content, are assigned to many meanings and their interpretation can depend on the situation. They are used mostly in the spoken language and concern a spontaneous reaction in a given situation. Certain emotions can be attributed to them such as joy, surprise, astonishment or anger. However, there are interjections that express emotions based on context. The research indicates that despite having a similar set of interjections in Swedish and Polish, the similarity between the two is ostensible, for instance, Swedish ‘aj’ and ‘oj’ express different emotions than Polish ‘aj’ and ‘oj’. Moreover, Swedish and Polish have specific interjections, which are not present in their counterpart. This causes the process of translation of these language units to be complicated and implies changes to the translation as compared to the original text.